1986
DOI: 10.1002/1098-108x(198609)5:6<969::aid-eat2260050602>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of maladaptive eating attitudes in a Canadian school age population

Abstract: Although cases of anorexia nervosa and bulimia are being seen increasingly by health care professionals, little data is available on the prevalence of these disorders in the general population of school age children. Using a validated eating attitude test (EAT), a total of 5150 students, aged 12–20, from public schools and one university in the Province of Manitoba were surveyed. Overall, 5% of males and 22% of females scored 30 or above on the scale, suggesting significant concerns and attitudes regarding eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
28
2
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 16 publications
(38 reference statements)
9
28
2
1
Order By: Relevance
“…The prevalence rate is also similar to those found in other western countries (Dancyger & Garfinkel, 1995;Lichener, Arnett, Rallo, Srikameswaran, & Vulcano, 1986;Patton, 1988;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Scheinberg et al, 1992;Toro, Castro, Garcta, Perez, & Cuesta, 1989;Whitaker et al, 1989;Wichstrom, 1995) and to those found in two studies conducted in Saudi Arabia (19.6% of the sample scored above 20) (Al-Subaie, 1998;Al-Subaie et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence rate is also similar to those found in other western countries (Dancyger & Garfinkel, 1995;Lichener, Arnett, Rallo, Srikameswaran, & Vulcano, 1986;Patton, 1988;Patton, Johnson-Sabine, Wood, Mann, & Wakeling, 1990;Scheinberg et al, 1992;Toro, Castro, Garcta, Perez, & Cuesta, 1989;Whitaker et al, 1989;Wichstrom, 1995) and to those found in two studies conducted in Saudi Arabia (19.6% of the sample scored above 20) (Al-Subaie, 1998;Al-Subaie et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings and those of Kinzl, Traweger, Trefalt, Mangweth, and Biebl (1998) and Leichner et al (1986) indicate that even at the prediagnosis (subsyndromal) level, there is an association between disordered eating and obesity. The findings suggest that despite body image concerns, drive for thinness, and inappropriate compensatory behaviors, our participants were not succeeding in terms of attaining or maintaining low weight.…”
Section: Discussionsupporting
confidence: 66%
“…However, another study (Whitaker et al, 1989) based on children in a single county in semirural New Jersey found no relationship between body weight or dieting behaviors and SES. No effect of social class on attitudes toward weight and dieting was observed in a school-age Canadian population (Leichner, Arnett, Rallo, Srikameswaran, & Vulcano, 1986). …”
mentioning
confidence: 97%